Microspectrophotometric quantitation of the diaminobenzidine reaction for histochemical demonstration of cytochrome oxidase activity - Cabrini, Rómulo Luis; Frasch, Carlos Alberto; Itoiz, María E. (The Histochemical Society, Inc., 1978)
Fil: Cabrini, Rómulo Luis Comisión Nacional de Energía Atómica; Argentina